Anestezjologia i intensywna terapiaBacteriological assessment of tip cultures of epidural catheters and the incidence of local infections during thoracic epidural analgesia – preliminary report - Misiołek, Hanna; Wilkowska, Jadwiga; Werner, Małgorzata; Wojciechowski, Grzegorz; Kucia, Hanna; Grządziel, Mateusz; Styrkosz, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: Continuous epidural analgesia is a well-established method of pain treatment after pulmonary resection by postero-lateral approach. Epidural catheter infection may be an important complication leading to central nervous system infection. The aim of this study was a bacteriological assessment of tip cultures of epidural catheters and the incidence of local infections during thoracic epidural analgesia in patients undergoing major thoracic procedures. Methods: 30 epidural catheters inserted for perioperative analgesia in patients aged 24-83 years were examined. Catheters were inserted into the thoracic epidural space using aseptic technique in the operating theatre. Epidural catheter care was conducted according to a protocol. Procedures were performed by 21 members of medical staff (doctors and nurses) from whom throat swabs were obtained before the study. All procedures of catheter implantation, time of epidural analgesia, local skin status, dressing changes and presence of local infection were documented. Upon completion of epidural analgesia, catheters were removed in aseptic conditions and their tips were sent for bacteriological culture. Results: The mean age of patients was 60±2 years. The epidural catheter was inserted at the level of Th4-Th5. The mean time of epidural analgesia was 6.5±1.8 days. Positive epidural catheter tip cultures were observed in 21 (70%) cases; in 13 (61.9%) cases Staphylococcus species was found. Signs of local infection were observed in 7 (23.3%) patients whose cultures were positive for Staphylococcus species. Time of epidural analgesia was not different from the other patients. Cases of systemic infection were not found. 28 (93%) patients were treated with an antibiotic for other reasons at the time when catheter tips were taken for culture. In 17 (81%) members of medical staff physiological bacterial flora was revealed in the throat swabs, and in 4 (19%) methicillin-susceptible Staphylococcus aureus was observed without clinical signs of infection. Conclusions: Positive epidural catheter tip cultures are frequent in patients undergoing thoracic operations – in some of these patients signs of local infection may develop. Bacteria isolated from epidural catheter tips represent physiologic skin flora. Precise assessment of infectious complications of thoracic epidural analgesia needs more studies.